Hysteresis loops observation of FePt and FePd square ferromagnets using micromagnetic simulation. Issue 1 (February 2020) - Fadhilah, U; Kurniawan, C; Djuhana, D
Abstract: In this study, we have investigated magnetic hysteresis loops of squared model FePt and FePd ferromagnets by a public micromagnetic simulation based on Landau-Lifshitz Gilbert (LLG) equation. The hysteresis loops of FePt and FePd ferromagnets are generated by in-plane and out-plane applied field with respect to the size and thickness variation. It is found that the coercivity field for both FePt and FePd squared ferromagnets exhibited different behavior for the size of ferromagnets around 50–100 nm and more than 100 nm. The results showed that the hysteresis loops produced a large coercivity when the in-plane field was applied and zero coercivity for external out-plane field. Interestingly, coercivity field was still observed for materials with size below 100 nm with ranging values between 20–40 mT. From this result, certain values of the coercivity field appeared for out-plane applied field at small thickness indicates a perpendicular magnetic anisotropy (PMA) behavior in FePt and FePd ferromagnets.